Search for prospects for the development of the hotel business on the example of the regions of Ukraine - Matviichuk, Liudmyla; Karpiuk, Iryna (Technology audit and production reserves, 2021)
The object of research is the processes of development of the hotel industry, as one of the most important elements of the tourist infrastructure of the regions. Let’s consider these processes using the example of the regions of Ukraine. One of the most problematic areas for the development of the hotel industry in the regions of Ukraine is the quality of hotel services and the condition of hotel rooms, which often do not meet international standards and norms. The number of business entities in the hotel business in Ukraine, in comparison with European countries, is also insignificant and during the period of large-scale events in the regions does not meet the demand for hotel services. In the work, research methods were used, which made it possible to determine the problem areas of the development of the hotel industry in the regions of Ukraine and propose ways to solve them. For example, to determine the content of the definition of «quality of hotel services», let’s use the method of generalization and systematization, to analyze the state and development of the hotel industry in the regions of Ukraine, let’s use the analytical method, etc. In the course of the study, a platform for the development of the hotel industry at the regional level was developed, taking into account the trends in the regional development of the hotel industry. This is due to the fact that the proposed process approach to the development of the studied processes has a number of advantages, in particular, the proposed software platform for the development of the hotel industry at the regional level provides for the choice of regional strategies for the development of the processes under study, taking into account the regional characteristics of the activities of hotel enterprises. Thanks to this approach, it is possible for hotel enterprises in the regions to unite into hotel or tourist clusters, hospitality associations, etc., in accordance with the presence in Ukraine of regions of leaders and regions of outsiders in the development of the hotel industry. Accordingly, the results can be useful both for the regions of Ukraine and beyond its borders, for better understanding and management in the current conditions of the pandemic.